2015
DOI: 10.3109/14397595.2015.1045255
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on the outcomes of MPO-ANCA-associated vasculitis in dialysis-dependent patients

Abstract: Pulmonary involvement was a predictor of relapse and mortality. Although relapse can occur long after the start of dialysis, incidence was low among dialysis-dependent patients. Prolonged maintenance immunosuppressive therapy might be limited to patients with pulmonary involvement in dialysis-dependent ANCA-associated vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In this study, we first demonstrated that the CONUT score estimated at diagnosis could predict all-cause mortality in AAV patients during follow-up, but it could not be used to prognosticate either relapse or ESRD occurrence. To date, an increased rate of all-cause mortality in AAV patients has been reported to depend on several baseline factors determined at diagnosis, including MPO-ANCA positivity, late-onset AAV, and the CRP-to-serum albumin and the albumin-to-globulin ratios 892223. We re-evaluated their clinical correlation to the all-cause mortality rate in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we first demonstrated that the CONUT score estimated at diagnosis could predict all-cause mortality in AAV patients during follow-up, but it could not be used to prognosticate either relapse or ESRD occurrence. To date, an increased rate of all-cause mortality in AAV patients has been reported to depend on several baseline factors determined at diagnosis, including MPO-ANCA positivity, late-onset AAV, and the CRP-to-serum albumin and the albumin-to-globulin ratios 892223. We re-evaluated their clinical correlation to the all-cause mortality rate in our study population.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the clinical course, survival rate, and relapse occurrence after the beginning of dialysis is scarce. Evidence suggests that vasculitis becomes quiescent after dialysis, and relapse rates seem to be much lower in these patients (reports range from 0.05 to 0.13 per person-year) [9][10][11][12]. Given the low rate of recurrence associated with the high risk of infection in ESKD patients, maintenance therapy is often unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Despite being a common complication of the disease, there are not many reports regarding the clinical course, survival rate, or relapse rate after beginning dialysis. Evidence suggests that vasculitis becomes quiescent after dialysis, and relapse rates seem to be much lower in these patients (reports range from 0.05 to 0.13 per person-year) [9][10][11][12]. The authors present 3 cases of AAV relapse in patients already on dialysis.…”
Section: Introductionmentioning
confidence: 99%
“…The risks of leukocytopenia and infection were lower in the RTX group than in the CY group in AAV patients with severe renal dysfunction ( 11 , 12 ). Pulmonary lesions, including AH, were shown to be the largest predictive factor for relapse and mortality in dialysis-dependent AAV patients ( 13 ). AH in AAV patients complicated with kidney failure like the present case is a critical issue, and its control is a problem directly related to the survival prognosis.…”
Section: Discussionmentioning
confidence: 99%